PENGERTIAN DAN IMPLEMENTASI INDIKATOR SERTA MATERI PEMBELAJARAN SKI UNTUK MTS DAN MA - Alizaa Zhafira, Cindy Elvira; Noorazmah Hidayati (STAI Nurul Falah Airmolek, 2024)
This article discusses the understanding and implementation of indicators and learning materials for Islamic Cultural History (ISH) for Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA). ISH is an important subject in shaping students' understanding of Islamic history and culture. In this study, we analyze various indicators used to evaluate the effectiveness of ISH learning, as well as explore relevant materials and their practical applications in the context of Islamic education. The methods used are literature study and curriculum document analysis to identify needs and challenges in implementing ISH learning. The results of the study indicate that a deep understanding of learning indicators can improve the quality of ISH education, as well as provide a strong foundation for students in understanding Islamic cultural heritage.Keywords: Definition, Implementation, Learning Indicators, Learning Materials, History of Islamic Culture, MTs, MA.